Prove by method of induction, for all n ∈ N
Answers
35=2n-1
2n-1-35
2n-36
n-36/2
n-18
Answer:
1² + 3² + 5² +.....................+(2n-1)² = (n/3)(2n-1)(2n+1)
Step-by-step explanation:
1² + 3² + 5² +.....................+(2n-1)² = (n/3)(2n-1)(2n+1)
p(1) = (2*1 - 1)² = (1/3)(2*1 - 1)(2*1 + 1)
=> 1² = (1/3)(1)(3)
=> 1 = 1
p(2) = 1² + (2*2 - 1)² = (2/3)(2*2-1)(2*2 + 1)
=> 1 + 3² = (2/3)(3)(5)
=> 10 = 10
let assume
p(k) = 1² + 3² + 5² +.....................+(2k-1)² = (k/3)(2k-1)(2k+1)
then
p(k + 1) =
1² + 3² + 5² +.....................+(2k-1)² + (2(k+1) - 1)²
= (k/3)(2k-1)(2k+1) + (2k + 1)²
= (2k + 1) ( (k/3)(2k-1) + (2k + 1) )
= (2k + 1) ( (k)(2k-1) + 3(2k + 1) )/3
= (2k + 1) ( 2k² - k + 6k + 3) /3
= (2k + 1) ( 2k² + 5k + 3) /3
= (2k + 1) ( 2k² + 2k + 3k + 3) /3
= (2k + 1) ( 2k(k + 1) + 3(k + 1)) /3
= (2k + 1) (2k + 3)(k + 1)/3
= ((k + 1)/3 )(2k+ 1)(2k + 3)
= RHS
Hence
1² + 3² + 5² +.....................+(2n-1)² = (n/3)(2n-1)(2n+1)